Свободные колебания системы, содержащей ферму Мизеса - Абрамов, К. В.; Михлин, Юрий Владимирович (НТУ "ХПИ", 2003)
Themethod of nonlinear normal modes is used to study nonlinear dynamics of mechanical system with snap-through truss. Mathieu's equation is derived to study the motions stability. The domain of instability of nonlinear normal mode is obtained
Keywords: прощелкивание; нелинейные колебания систем; осциллятор; локализованные периодические движения; нелокализованные движения; устойчивость периодических движений